Tendencje rozwojowe polskiego importu i eksportu w latach 1950—1960 - Kulik, Czesław (Wydział Prawa i Administracji UAM, 1966)
The article presents the results of the analysis of the size and structure of Polish import and export in the years 1950—1960, taking into consideration particulary the trends of individual sections. As well in import as in export there is a distinct and permanent tendency to increase returns in the whole investigated period, but it differs in separate sections. It is possible to demonstrate many of them approximately with the aid of Ezekiel's function in the shape of: log Y=a+bX. In some cases it was necessary to apply the higher degree of functions as: Y=a+bX+cX2 Y = a + bX+cX2+dX3 or log Y=a+bX+cX2+dX3 etc. For estimation of constants for this type of functions it was necessary to apply the matrix calculus. The paper gives as an example the review of different types of functions in order to show the possibility of adapting statistical methods in plannig and in the economic policy of foreign trade for setting suitable prognoses and for adopting home economy to the requirements visible in the investigated field.